74 Left ventricular remodelling post transcatheter aortic valve implantation (TAVI) is dependent on baseline mean gradient and ejection fraction: an echocardiographic study. (June 2018) - Badiani, Sveeta; Zalen, Jet van; Ramasamy, Anantharaman; Ozkor, Mick; Mathur, Anthony; Kennon, Simon; Mullen, Michael; Bhattacharyya, Sanjeev; Lloyd, Guy
Abstract : Background: The left ventricular response to aortic stenosis (AS) is complex. Although transcatheter aortic valve implantation (TAVI) decreases the left ventricular afterload by reducing the transvalvular pressure gradient, data regarding its impact on left ventricular geometry is limited. This study sought to assess left ventricular reverse remodelling following transcatheter aortic valve implantation (TAVI). Methods: Data from patients with severe aortic stenosis (AVA <1 cm²) undergoing TAVI at our institution was analysed. Patients without both an in-house pre-and post procedure echocardiogram available for analysis were excluded, as were patients with suboptimal echocardiographic windows. Comprehensive echocardiography was performed prior to and following intervention. Patients were classified into 4 subtypes according to mean gradient and LVEF: HGNEF: High gradient (MG >40 mmHg) and normal ejection fraction (LVEF >55%) HGREF: High gradient (MG >40 mmHg) and reduced ejection fraction (LVEF <55%) LGNEF: Low gradient (MG <40 mmHg) and normal ejection fraction LVEF >55% LGREF: Low gradient (MG <40 mmHg) and reduced ejection fraction (LVEF <55%) Results: 67 patients were included in the final analysis. The mean age was 80.8±7.5 years and 37 patients (55.2%) were female. The median follow up time for echocardiography was 11.1 weeks (IQR 7.6–15.7 weeks). The number of patients were subdivided into: 1. HGNEF 38 (56.7%), 2. HGREF: 13 (19.4%), 3. LGNEF: 4 (6%) and 4. LGREF: 12 (17.9%). Overall, there was a significant reduction in septal thickness and left ventricular mass on the follow up echocardiogram. The decrease in relative wall thickness was not significant: Interventricular septum (mm): Pre-TAVI 12.3±2.7 vs Post TAVI 11.7±2.6, p=0.027 Posterior wall (mm): 10.8±2.3 vs 10.4±2 p=0.166 LVEDD (mm): 46.3±7.6 vs 45.6±9.4, p=0.867 RWT: 0.49±0.15 v's 0.46±0.14, p=0.159 LV mass: 199±59 vs 186±51, p=0.016 Patients with high gradient aortic stenosis and preserved left ventricular ejection fraction showed greater decreases in relative wall thickness and left ventricular mass than those with high gradients and reduced ejection fraction and those with low gradient aortic stenosis. Group 1, HGNEF. Pre TAVI RWT 0.53±0.15 vs Post TAVI RWT 0.47±0.13, Pre TAVI LV mass 188±51 vs 174±48, p=0.028. Group 2, HGREF. RWT 0.42±0.17 vs 0.44±0.15, LVM 223±70 vs 211±60, p=0.345. Group 3, LGNEF. RWT 0.47±0.1 vs 0.52±0.23, LVM 178±28 vs 187±60, p=0.854. Group 4, LGREF RWT 0.42±0.09 vs 0.43±0.13, LVM 215±68 vs 93±39, p=0.308. Conclusions: Our data demonstrates a significant improvement in left ventricular mass following TAVI, which appears to be driven by a reduction in wall thickness. Sub-group analysis suggests that the improvements in left ventricular geometry are more pronounced in patients with high gradient aortic stenosis and preserved ejection fraction.